THE PARTNERSHIPS BETWEEN SCHOOL AND PARENTS TOWARD STUDENT LEARNING ACHIEVEMENT AT SMAK MEKAR - Ros Ratna Lawolo; Hidayati Daeli; Kristof Martin Efori Telaumbanua; Riswan Zega (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to examine the partnership between schools and parents in supporting student learning achievement at SMAK Mekar. The formulation of the problems studied include: how the partnership between schools and parents on student achievement. Factors inhibiting effective partnerships, and the impact of partnerships on student motivation and confidence. The research method used is qualitative with data collection techniques through questionnaires, observation and in-depth interviews with teachers, parents, and students, as well as questionnaires to obtain an overview of participation and obstacles faced. The results show that good partnerships, such as regular communication and active participation of parents, have a positive effect on students' academic achievement and motivation. The main obstacles include geographical distance, parents' lack of understanding of the subject matter, and the perception that their participation is not important. Consequently, students who receive support from their parents tend to have higher self-confidence and motivation to learn. This study recommends the importance of improving communication and socialization of the role of parents to strengthen effective partnerships to improve student achievement and character at SMAK Mekar.